THE ROLE OF THE HAMLET HEAD IN THE DELIBERATION IN TILONGGIBILA VILLAGE PINOGU DISTRICT, BONE BOLANGO REGENCY - nurdjana thalib; William Indra S Mooduto; Sitti Husna Noviana Djou (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The purpose of this study was to determine the role of the hamlet head in village meetings and to determine the factors that influence the implementation of the deliberation process in Tilonggibila village. The research method in writing this final report is a descriptive qualitative method with the type of field research. The data collection techniques used are observation, interviews and documentation which are primary data, which comes from eight informants who provide direct information regarding the role of the hamlet head in village deliberations. From this research, it can be concluded that the role of the Hamlet Head as a motivator and facilitator in village deliberations has been carried out in accordance with his duties, authorities and functions as the Dusun Head to motivate residents, facilitate residents in deliberation activities in the village. The problem that becomes an obstacle in the implementation of deliberation or the maximum role of the hamlet head in motivating and facilitating the community is the lack of community participation due to the lack of awareness and understanding of the community who have the will, willingness, awareness, and cooperation between the government and the community in realizing good governance. transparent and participatory.